2009
DOI: 10.1117/12.830180
|View full text |Cite
|
Sign up to set email alerts
|

A new simultaneous compression and encryption method for images suitable to recognize form by optical correlation

Abstract: In some recognition form applications (which require multiple images: facial identification or sign-language), many images should be transmitted or stored. This requires the use of communication systems with a good security level (encryption) and an acceptable transmission rate (compression rate). In the literature, several encryption and compression techniques can be found. In order to use optical correlation, encryption and compression techniques cannot be deployed independently and in a cascade manner. Othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Several authors have demonstrated that significant compression of encrypted data can be obtained in the general case [2,[7][8][9][10][11][12][13]. In specific situations, the authors claim that the same code rate is achievable by encrypting before compressing as compressing before encrypting.…”
Section: Introductionmentioning
confidence: 98%
“…Several authors have demonstrated that significant compression of encrypted data can be obtained in the general case [2,[7][8][9][10][11][12][13]. In specific situations, the authors claim that the same code rate is achievable by encrypting before compressing as compressing before encrypting.…”
Section: Introductionmentioning
confidence: 98%
“…Understanding and optimizing optical processing of information techniques is one of the fundamental issues in communication and information technologies [1][2][3][4][5][6][7][8] . Several methods based on spatial filtering have been used to encrypt images.…”
Section: Introductionmentioning
confidence: 99%
“…Significant compression of encrypted data occurs in some cases [4][5][6][7][8][9][10][11][12], and in specific situations, encrypting before compressing produces the same code rate as compressing before encrypting. In the special case of compression of a Gaussian distributed source with a mean-squared error fidelity criterion, the encrypted file compresses to the same entropy rate as the original source [13].This applies to both lossless and lossy compression, but not, in general, to data that deviates from Gaussian source conditions.…”
Section: Introductionmentioning
confidence: 99%